Leo Strauss and the recovery of medieval political philosophy - Parens, Joshua, 1961- (Rochester studies in medieval political thought, 2016)
Leo Strauss is one of the foremost political thinkers of the twentieth century, known primarily for reviving the study of classical political philosophy. Strauss recovered that tradition of thought largely lost to the West because he did not emphasize its metaphysical teachings but its teaching on politics. What brought Strauss to his reading of the classics, however, was a discovery he made as a young political scientist studying the obscure texts of Islamic and Jewish medieval political thought. In this volume, Joshua Parens examines Strauss's investigations of medieval political philosophy, offering interpretations of his writings on the great thinkers of that tradition, including interpretations of his most difficult writings on Alfarabi and Maimonidies. In addition Parens explicates Strauss's critique of Scholasticism, and explains why Strauss in his study departed from Christian medieval thought. Contrasting Scholasticism with Islamic and Jewish medieval political philosophy, Parens clarifies the theme of Strauss's thought, what Strauss calls the "theologico-political problem," and reveals the significance of medieval political philosophy within the Western tradition